Analysis of the Effect of Good Corporate Governance Mechanism, Size, and Audit Quality on the Acceptance of Going Concern Audit Opinions - Tanggor Sihombing; Nahda Annisa Rafael (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This researh aims to analyze the influence the effect of independent commissioner, managerial ownership, institusional ownership, audit quality, size and audit committee on the acceptance of going concern opinion on real estate companies that have been listed on S&P Capital in 2016-2020. The population used in this reseach are all real estate companies listed on www.capitaliq.com in the five year period, bertween 2016-2020 with 23 companies. The sampling method used in this reseach is using purposive sampling method to obtain 115 sample. The data analysis method used in this reseach is logistic regression. The results of this study explain that independent commissioners, company size and audit committee effect on the acceptance of going concern audit opinions, while managerial ownership, institutional ownership and audit quality not affect the acceptance of going concern audit opinions.